Wybrane zagadnienia i charakterystyka produktów ubezpieczeniowo-inwestycyjnych (unit-linked life insurance) - Pisarewicz, Piotr (Selected Issues and Characteristic of Unit-Linked Life Insurance Products, 2008)
Paper focus on selected issues of "unit-linked life insurance products" ("universal life") on Polish market. Study describes structure of this products based on separation of insurance and investment dements of unit-linked policies'. In addition author describes definition of insurance capital funds (compared with investment funds), legal requirements of insurance contracts (agreements), publication of financial statements, rules of insurance benefits and claims, etc.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 352-358